Cement-Based Composites Advancements in Development and Characterization - Sikora, Pawel; Chung, Sang-Yeop (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue on "Cement-Based Composites: Advancements in Development and Characterization" presents the latest research and advances in the field of cement-based composites. This Special Issue covers a variety of experimental studies related to fiber-reinforced, photocatalytic, lightweight, and sustainable cement-based composites. Moreover, simulation studies are presented in this Special Issue to provide fundamental knowledge of designing and optimizing the properties of cementitious composites. The presented publications in this Special Issue show the most recent technology in the cement-based composite field.